The effect of digital media on elementary school students' ecoliteracy development - Ivanka, Windy; Cahaya Nurani, Dwi (EduStream: Jurnal Pendidikan Dasar, 2025)
This study aims to evaluate the effect of digital media use on the development of ecoliteracy of elementary school students. Digital media offers an interactive and interesting method way to deliver ecological concepts, that make students easy to understand the relationship between living things and the environment. This study used quantitative approach with a pre-experimental design of one group pretest-posttest design. The subjects of this study were fifth grade elementary school students in North Indralaya City, Indonesia. Data were collected through multiple-choice tests consisting of pretest and posttest, each consisting of 10 questions to measure students' abilities before and after treatment. The results of this study showed that the average pretest score was 44.28 and 80 in post-test, it was found that 17 students achieved the Minimum Completion Criteria after treatment. Hypothesis testing using the Paired Sample T-Test showed a significance of 0.000, which means there is a significant difference between the pretest and posttest scores. This study concludes that the use of digital media has a positive effect on the development of students' ecoliteracy, which can help them understand ecological concepts and increase environmental awareness